Comparison of selected physical performance characteristics of elite young Turkish and Indonesian badminton players - Özgür, B. (International Journal of Applied Exercise Physiology, 2020)
The goal of this study was to compare the physical performance characteristics of elite young Turkish and Indonesian badminton players. Eleven Turkish (age 16.09±1.04, height 172.70±5.43 cm, body weight 65.07±8.55 kg) and twelve Indonesian (age 17.17±1.11, height 175.42±5.71 cm, body weight 68.50±8.27 kg) elite male badminton players participated voluntarily in this study. Height, body weight, body mass index was measured and standing long jump, overhead medicine ball throw (2 kg), back strength, leg strength and dominant hand-grip strength tests were performed to the athletes. The results of the analysis have shown that leg strength values of Turkish athletes were significantly higher than those of Indonesians (p<0.05), while other characteristics were similar (p>0.05). The current study indicates that it is more important to focus on the technical, tactical and motivational characteristics of Turkish badminton players and other country players of the same level in order to improve their performance to the high level.